Analisis NPK Pupuk Organik Cair Limbah Ikan Nila dengan Pemanfaatan Mikroorganisme Lokal Kulit Pepaya - Galih Dwiyogo Wicaksono; Siti Hanggita Rachmawati (Universitas Sriwijaya, 2022)
Liquid organic fertilizer is an organic fertilizer made in liquid with the aim to ease the process absorption of nutrients by plants because the nutrient content in liquid organic fertilizer has been decomposed. This study aims to utilize waste viscera of tilapia (Oreochromis niloticus) as a raw material in the making process of liquid organic fertilizer and find effect of concentration differences of papaya peel (Carica papaya L.) as local microorganisms (MOL) on the nutrient content of liquid organic fertilizers. The research used a randomized block design by 4 treatment levels and 3 replications. The treatment was the difference in concentration of papaya peel as MOL i.e. A1 (0%), A2 (25%), A3 (50%) and A3 (75%). The parameters observed were the content of macronutrients nitrogen (N), phosphorus (P) and potassium (K) in liquid organic fertilizer. The results showed that the maximum levels of N, P and K in this study were nitrogen (N) levels of 0.143% the addition of 75% MOL papaya peel, phosphorus content (P) 0.030% the addition of 25% MOL papaya peel and potassium (K) content of 0.070% the addition of 75% MOL papaya peel. The results of this study, the best treatment was A3 by addition 75% MOL papaya peel.